The Ramsey cooperative and non-cooperative unconventional monetary policy - Shifu Jiang (FIW - Research Centre International Economics, 2017)
I study the Ramsey problem for three unconventional monetary policies in a twocountry model. An equity injection into financial intermediaries is the most efficient policy. Due to precautionary effects of future risk, a central bank should exit from these policies in accordance with but slower than the speed of deleveraging in the financial sector. The optimal policy is changed considerably if cross-country policy cooperation is not imposed. In this case, the unconventional interventions tend to be too strong in one country but too weak in the other. The cooperation gain is a function of policy cost. At last, I evaluate several simple rules and find that the rule responding to gaps in asset prices mimics the optimal policy very well.
Keywords: E44; E58; F41; F42; C63; 330